Simplicity as a Strategy-Making Process: The Effects of Stage of Organizational Development and Environment on Performance - Lumpkin, G. T.; Dess, Gregory G. (Academy of Management Journal, 1995)
This field study investigated the importance of simplicity as a strategy-making process. Consistent with our hypotheses, use of a simplistic strategy-making process was found to be positively associated with performance during early stages of organizational development but detrimental to performance as organizations grew and matured. Simplicity was also found to be negatively related to performance in dynamic environments; in heterogeneous environments, it seemed lo be adversely related to performance only in later stages of organizational development.